Pelaksanaan Ekstrakurikuler Paduan Suara Di SMA Adabiah 2 Padang - Badrianti Anugrah Putri; Ardipal Ardipal (FBS Universitas Negeri Padang, 2021)
This study aims to describe the implementation of the choir extracurricular at SMA Adabiah 2 Padang. This is a qualitative research with a descriptive analysis approach. The research instrument used was the researcher itself and was assisted by supporting instruments such as writing instruments and cameras. The data were collected through observation, interviews, documentation, and literature study. The data analysis was conducted by collecting the data, clarifying the data, and concluding the data. The results show that the implementation of choir extracurricular activity at SMA Adabiah 2 Padang run well due to the fact that it was conducted through the correct stages, starting from gathering students who were interested in choir extracurricular activities, scheduling, training agendas, and giving materials. In the implementation stage of the choir, students can sing the Ayam Den Lapeh song in a choir which consists of two voices, soprano and the alto voice. The choir extracurricular activity was held for the first time at SMA Adabiah 2 Padang, but the results are quite good because it was supported by sufficient facilities. Eventhough they do not have a permanent trainer, the teacher has been able to carry out these extracurricular activities well.